Transferências intergovernamentais da união para os Estados : uma análise dos repasses fiscais e dos critérios de distribuição adotados no período 2007-2016 e uma proposta alternativa visando à equalização fiscal - Reis, Paulo Henrique Amâncio (2019)
The current model of intergovernmental transfers from the Union to the states is extensive and complex, in which various composition, objectives and distribution criteria are observed. By this structure interjurisdictional socioeconomic differences tend to be maintained or reinforced, which engender unequal provision of public goods in the territory. In view of this perspective, this paper intends to propose and test a new methodology for fiscal transfers that can balance the conditions of public offering between states. The proposed model is based on fiscal equalization, in which the precepts of the fiscal federalism literature are appraised and the conditions and results of the countries that apply this method are examined. In this purpose, the research presents the foundations of the First and Second Generation Theory of Fiscal Federalism and its contributions about tax equalization; analyzes the individual and joint result of fifteen fiscal transfers of the Union to the states and designs a fiscal equalization model that is appropriate given the specificities of the brazilian tax system.